A dependência de estado na extinção de memória aversiva: participação do núcleo do trato solitário, hipocampo e amígdala - Rosa, Jessica (2014)
We investigate whether the extinction of inhibitory avoidance (IA) learning can be subjected to endogenous state-dependence with systemic injections of epinephrine (E), and whether endogenous norepinephrine (NE) and the Nucleus Tractus Solitarius NTS → Hippocampus/Amygdala (HIPP/BLA) pathway participate in this. Thus, rats trained in Inhibitory Avoidance Learning (IA; 0,5 mA/2s) were submitted to session of extinction 24 h apart: the animals were placed to the same apparatus but without the footshock. 24 h after the extinction session, they were tested for the retention of extinction. Results indicate that post-extinction training E (50 or 100 μg/kg) induced a poor retrieval of extinction in the test session of this task unless an additional E injection (50 μg/kg) was given prior to the extinction test. This suggested state-dependence. Muscimol (0,01 μg/side) microinfused into the NTS prior to the extinction test session blocked E-induced state-dependence. Norepinephrine (NE, 1 μg/side) infused bilaterally into NTS restores the extinction impairment caused by post-extinction training i.p. E. In animals that received post-extinction training injections E and 6 min before the extinction test bilateral NTS blockade induced by muscimol plus NE (1 μg/side) into the CA1 region of the dorsal hippocampus or into the basolateral amygdala restored the normal extinction levels that had been impaired by muscimol. These findings suggest that the state-dependence occurs during the extinction of the fear memory and that are a role for the NTS → HIPP/BLA pathway in the retrieval of extinction.